2019
DOI: 10.1167/iovs.18-26441
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography in Mice: Quantitative Analysis After Experimental Models of Retinal Damage

Abstract: PURPOSE. We implemented optical coherence tomography angiography (OCT-A) in mice to: (1) develop quantitative parameters from OCT-A images, (2) measure the reproducibility of the parameters, and (3) determine the impact of experimental models of inner and outer retinal damage on OCT-A findings. METHODS. OCT-A images were acquired with a customized system (Spectralis Multiline OCT2). To assess reproducibility, imaging was performed five times over 1 month. Inner retinal damage was induced with optic nerve trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…Numerous other studies in rodents investigating retinal degeneration after ONC also found a decrease of the RNFL and TRT, as well as a loss of retinal ganglion cells (26)(27)(28)(29). After a light-induced retinal damage, authors essentially found degeneration of the ORL and photoreceptors, in line with our results (30,31).…”
Section: Discussionsupporting
confidence: 92%
“…Numerous other studies in rodents investigating retinal degeneration after ONC also found a decrease of the RNFL and TRT, as well as a loss of retinal ganglion cells (26)(27)(28)(29). After a light-induced retinal damage, authors essentially found degeneration of the ORL and photoreceptors, in line with our results (30,31).…”
Section: Discussionsupporting
confidence: 92%
“…33,34 All the linear-scale images were denoised, binarized, and skeletonized prior to the quantitative analysis. 35 BVD is defined as the ratio of the total image area occupied by the vasculature to the total area in an OCTA image…”
Section: Omag Algorithmmentioning
confidence: 99%
“…Similar to the approach of Smith et al, 15 , and total retinal thickness [TRT]) and three vascular plexi (SVC, ICP, and DCP) was conducted using the automated software in-built into the imaging platform (Heidelberg Engineering). Each volume was checked for segmentation errors.…”
Section: Image Processing and Analysismentioning
confidence: 99%
“…The advent of optical coherence tomography angiography (OCTA) has facilitated clinical and laboratory studies of the normal trilaminar vasculature 2,13,14 and the impact of a range of retinal conditions on the vasculature. [15][16][17] A number of investigations have used OCTA to investigate how the retinal and optic nerve vasculature responds to acute IOP elevations. 18 Zhang et al 19 showed in human subjects, that IOP elevation of 10 to 15 mm Hg above baseline induced via a dark-room prone test did not affect OCTA vessel density.…”
mentioning
confidence: 99%